Examining the State of Community-led Development Programming - Veda, Gunjan; Trandafili, Holta; Zuniga, Martha Cruz (2021)
Gunjan Veda, Holta Trandafili and Martha Cruz Zuniga POLICY SEMINAR Examining the State of Community-led Development Programming Co-Organized by IFPRI and Movement for Community-led Development APR 7, 2021 - 09:30 AM TO 11:00 AM EDT